Haemato-biochemical response and hormonal profile of rabbit does drenched varying levels of clove (syzygium aromaticum) powder - Amao, E. A.; Amao, O.D.; Agbaye, F.P.; Tolani, T.E.; Omoboko, D.; Ilesanmi, S.G.; Rafiu, M.A. (Nigerian Journal of Animal Science, 2023)
Use of phytogenic feed additives in livestock industry is gaining ground, there is need to evaluate its effect on reproductive hormone, hematology and serum biochemistry of animals placed on phytogenic additive. Clove powder supplementation was investigated on haemato-biochemical and hormonal response of crossbred rabbit does (Oryctolagus cuniculus) in a 8-weeks drenching trial. An experiment was conducted on twenty - four rabbits of 5months of age. The animals were drenched with clove powder to determine its effect on the biochemical response and hormonal profile of the rabbits. The twenty- four rabbits were allotted into three treatments of four replicates in a completely randomized design. Dietary levels of 0.0g, 0.5g and 1.0g of clove powder were given orally to the rabbits. Blood samples were collected from the lateral saphenous vein at the end of the experiment to evaluate haemato-biochemical parameters and hormonal profile. Data collected on haemato-biochemical parameters and hormonal profile were subjected to one way analysis of variance. Some of the parameters evaluated were: Red blood cell, White blood cell, Pack cell volume, Total protein, Globulin, Aspartate aminotransferase, Alanine aminotransferase, Blood urea nitrogen, Creatinine trimethylglycine, estradiol, luteinizing hormone, Follicle stimulating hormone and Progesterone. All Haematological parameters showed significant (P<0.05) differences in favor of animals on 1.0g of clove powder except for white blood cell. Parameters such as Albumin, Alkaline phosphatase, Cholesterol, high density lipoprotein, Low density lipoprotein and Albumin: Globulin shows no significant difference (p>0.05). Estradiol and Follicle stimulating hormone showed significant differences (p<0.05), they follow same trend. Lutenising hormone and progesterone shows significant differences (p<0.05). It was concluded that up to 1.0g of clove can be included in rabbit’s diet without any detrimental effect on their health status.